US EDUCATIONAL FOREIGN POLICY AS A “SOFT POWER” FACTOR: RETROSPECTIVE ASPECT - Panfilov, Oleksandr; Savchenko, Olga (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2021)
The subject of the article is education as a component of US foreign policy that was used and still is as an efficient and influential factor in the development of society oriented to American values, viewpoints, and way of life. The goal of the article is to analyse the place and role of education in the US foreign policy strategy in the modern era, while the main objectives are to specify the strategic directions of using education as a “soft power” by the United States as well as identify specific mechanisms that enable achieving the most effective results in this direction. Within the study, all the above objectives are solved. In particular, the main results obtained include the following: the historical context of the US use of education as a “soft power” tool is studied, the strategic directions of using educational potential as a “soft power” are analysed, the areas where educational efforts of the United States have always been concentrated are singled out. The US experience in the sphere of educational services export can be used to specify and theoretically substantiate the capabilities of Ukraine to advance its interests in the international arena using the educational opportunities our country can suggest to the world.